Condylomata acuminata/Luetic flat condylomata. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The differential diagnosis between condylomata acuminata, an infection caused by Papova virus, and flat condylomata due to early congenital syphilis in the newborn period has been largely debated in the past.